Carbohydrate chemistry, biology and medical applications - Garg, Hari G., 1931-; Cowman, Mary K.; Hales, Charles A., 1941- (Elsevier, 2008)
The finding by Emil Fischer that glucose and fructose on treatment with phenylhydrazine gave the identical osazone led him to the elucidation of stereochemistry of carbohydrates. Since then, progress in the field of carbohydrates has been amazing with the unraveling their basic structure, biosynthesis, immunology, functions, and clinical uses, for pure carbohydrates and for protein-linked carbohydrates (glycoproteins and proteoglycans). The chapters in this book present a logical sequence leading from the chemistry and biochemistry of carbohydrates, followed by their role in various pathological conditions, to carbohydrates as potential therapeutic and diagnostic agents. This book offers a detailed panoramic review of the chemistry and biology of carbohydrates for chemists, biologists and health professionals. Each chapter is authored by contributors expert in the particular area of research.
Includes index.
Keywords: sacharidy; metabolismus sacharidů; výživa člověka; carbohydrates; sacharide metabolism; human nutrition; elektronické knihy; electronic books